Stochastic Steady-State Security Assessment for Power System Operation by Chance Constrained Optimal Power Flow-Based Load Shedding - Zhou, Xinyu; Jiang, Yingying; Yang, Chen; Xu, Dan; Tang, Junjie; Xie, Kaigui (Frontiers in Energy Research, 2022)
The operational uncertainty of power system is significantly increased by the high penetration of renewable energy and diversification of load behavior, which have aroused the novel research on stochastic steady-state security assessment (SSSA) urgently when the operational condition gets worse and contingency happens more frequently. First of all, a novel contingency analysis model has been proposed based on chance constrained optimal power flow (CCOPF) in this paper, which is able to give a comprehensive consideration on conventional generator outage, uncertainty of system operation and load shedding of interruptible loads (ILs). Moreover, the proposed model is very practical and can be solved much efficiently by an iteration method, so that the purpose of secure system operation after contingency can be better realized. Secondly, to further enhance the steady-state security of system, a novel pricing method for ILs has been developed by this paper. In addition, a composite contingency ranking index has been also established to reflect the severity of generator outage more accurately. Finally, extensive study results based on a modified IEEE-39 test system have demonstrated the validity of the proposed model, which can hold a good balance amongst security, economy, controllability, and maneuverability.